2005
DOI: 10.1093/eurheartj/ehi503
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of myocardial perfusion scintigraphy as gatekeeper for invasive examination and treatment in patients with stable angina pectoris: observational study without post-test referral bias

Abstract: The use of MPS as gatekeeper appears to make about half of catheterizations and almost one-fifth of revascularizations redundant. Even in high-risk groups, substantial savings are possible, and the risk of overlooking patients with severe disease seems negligible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 19 publications
1
21
0
2
Order By: Relevance
“…Moreover, the rare occurrence of false negative S-MPI for LMT lesion or 3-vessel disease, with a frequency of around 2% of normal S-MPI, has been reported. 24, 25 Among the 31 patients with normal S-MPI in our study, postischemic stunning was observed in only 1 (3%) patient with 3-vessel disease as identified by CCTA.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, the rare occurrence of false negative S-MPI for LMT lesion or 3-vessel disease, with a frequency of around 2% of normal S-MPI, has been reported. 24, 25 Among the 31 patients with normal S-MPI in our study, postischemic stunning was observed in only 1 (3%) patient with 3-vessel disease as identified by CCTA.…”
Section: Discussionmentioning
confidence: 61%
“…That means that not every patient after myocardial infarction had an evident fi xed perfusion defect on gated-SPECT of myocardium. The above-men-tioned number of patients with a nonviable myocardium is nevertheless larger than for instance the patient group of Hoilund-Carlsen et al (8 % of 168 revascularized patients with a stable angina pectoris) 16 . This fact is in our study caused by a selection of patients with a systolic LV dysfunction with a large number of patients after myocardial infarction.…”
Section: Discussionmentioning
confidence: 70%
“…Referral patterns may differ too. Thus, in a consecutive series of 972 patients referred for CA for known or stable angina, 40% had normal angiograms (16), ie, approximately twice the rate reported in Canada (38) but lower than the 44% reported a few years earlier in the United States (39).…”
Section: Discussionmentioning
confidence: 88%